Children, citizenship and environment : nurturing a democratic imagination in a changing world - Hayward, Bronwyn. (Routledge, 2012)
"Today's millennial generation inherit a world confronted by four difficult and intersecting challenges: dangerous environmental change, weakening democracies, growing social inequality, and a paradigm of economic growth that has contributed to unprecedented youth unemployment and resource extraction beyond our planet's limits. But the future is not inevitable and today on the streets everywhere; there is a strong, youthful energy for change. 'Children, Citizenship and Environment' sets out a new agenda for citizenship education which reflects both the responsibility and opportunities we are confronted with to support young citizens. In a myth busting discussion of issues facing young citizens growing up in neoliberal democracies, political scientist Bronwyn Hayward draws on the experience of New Zealanders, a nation where young citizens often express a strong sense of personal responsibility for their planet but where many face shocking social conditions. Theoretically informed and written with engaging practical insight, Hayward argues that young citizens today will need fewer lessons in how to recycle or when to switch off the lights and more intergenerational support to reclaim their democratic imagination and discover the 'seeds' of ecological citizenship and their own SMART ' handprint' for social justice. This book will be of interest to a wide audience including teachers in the Education sector, students and researchers, as well as policy makers and N.G.Os who work in the area of Youth Citizenship"--